2015
DOI: 10.1155/2015/287693
|View full text |Cite
|
Sign up to set email alerts
|

Propolis Is an Efficient Fungicide and Inhibitor of Biofilm Production by VaginalCandida albicans

Abstract: Vulvovaginal candidiasis (VVC) is one of the most common genital infections in women. The therapeutic arsenal remains restricted, and some alternatives to VVC treatment are being studied. The present study evaluated the influence of a propolis extractive solution (PES) on biofilm production by Candida albicans isolated from patients with VVC. Susceptibility testing was used to verify the minimum inhibitory concentration (MIC) of PES, with fluconazole and nystatin as controls. The biofilm formation of 29 vagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 40 publications
(52 reference statements)
5
60
1
4
Order By: Relevance
“…Capoci et al . () evaluated propolis influence on the biofilm produced by C . albicans isolated from patients with vulvovaginal candidiasis, suggesting that it may have additional benefits in the treatment of this infection.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Capoci et al . () evaluated propolis influence on the biofilm produced by C . albicans isolated from patients with vulvovaginal candidiasis, suggesting that it may have additional benefits in the treatment of this infection.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…The propolis source was as described by Capoci et al [15], with green propolis collected from hives of A. mellifera in Cianorte (Paraná, Brazil). The samples were triturated and stored at -20 • C until further analysis.…”
Section: Pe and Phenol Contentmentioning
confidence: 99%
“…In vitro antifungal susceptibility testing of planktonic cells was performed using a microdilution method adapted from Capoci et al [15] and the Clinical and Laboratory Standards Institute M38-A2 protocol [17] with serial dilution of PE 34.17, 68.35, 136.71, 273.43, 546.87, 1093.75, 2187.5, 4375, 8750 and 17,500 μg ml -1 of TPC expressed in gallic acid in RPMI 1640 (Roswell Park Memorial Institute; Gibco, NY, USA) with l-glutamine (with sodium bicarbonate) and 0.165 M 3-(N-morpholino) propanesulfonic acid (pH 7.2) as a buffer (Sigma-Aldrich). The strains of Fusarium spp.…”
Section: Antifungal Assaymentioning
confidence: 99%
“…Capoci et al (2015) (20) observed a reduction of more than 50% of CFUs for all Candida albicans isolates after exposure to Propolis Extract (PES) compared to control. These results corroborate those found in this research, where there was also a reduction of CFUs of C. albicans, C. tropicalis and C. parapsilosis at 25 and 250 μg / mL at all abiotic materials tested.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate antifungal activity, 50mg of EPP was diluted in 500μl of DMSO, from this dilution it was prepared a working solution by diluting 1ml in 9ml of PBS 1x, from which concentrations of the extract of 0.25, 2.5, 25 and 250μg / mL were obtained. Inhibition halos were evaluated according to interpretation criteria of CLSI (2009) (25) and Capocci (2013) (20).…”
Section: Methodsmentioning
confidence: 99%